Implementasi Struktur Data Queue Dan Stack Dalam Sistem Antrian Kasir Cafe Berbasis Web - Akbar Alif Haikal; Khairany Zuhriyyah Jinan Hsb; Syti Salwaa Nafiisah; Akram Fauzan; Fanny Ramadhani (Pusat Riset dan Inovasi Nasional, 2026)
An effective queuing system is one of the key factors in improving service quality in a cafe, particularly at the cashier section. This study discusses the implementation of queue and stack data structures in a web-based cashier queuing system. The queue structure is applied to manage customer service in a First In First Out (FIFO) manner, ensuring that each customer is served according to their arrival order. Meanwhile, the stack structure is implemented to handle special needs such as transaction cancellation or repeating the most recent data with the Last In First Out (LIFO) concept. The system development method uses web programming languages (HTML, CSS, JavaScript) for data storage. The results show that the combination of queue and stack structures simplifies queue management, reduces errors in transaction recording, and improves cashier service efficiency. Thus, this system can serve as an innovative solution for queue management in small to medium-sized cafés.